Methodological Aspects of Classification of Environmental Impacts Caused by russian Aggression in Ukraine - Didukh, Ya. P.; Maruniak, Eu. O.; Lisovskyi, S. A.; Kuzemko, A. A.; Chekhnii, V. M. (Ukrainian Geographical Journal, 2024)
The article examines environmental impact assessment, covering the historical context as well as current risks and threats posed by the war in Ukraine. The author analyzed studies that directly address the impact of military operations on the environment. Particular attention has been paid to regulatory documents approved in Ukraine after 2022, including the Government of Ukraine’s resolution regulating the cost assessment of damages, which identified several gaps in the environmental components. The authors identify seven types of impact arising from certain aspects, in particular: by the nature of the factors’ action; by time; by intensity; by territorial scale; by the form of territorial manifestation; by the nature of the consequences; and by the possibility of returning to the previous state. A classification of military impacts (explosions, mining, movement of military equipment, etc.) and their potential consequences for various environmental components has also been proposed. The general methodology is also specified for individual components and adapted to assess ecosystem losses, illustrated using a habitat score.